Comparing service quality between private and public hospital / Nazhatul Aini Mohd Farid - Mohd Farid, Nazhatul Aini (Faculty of Business and Management, 2009)
This research is conducted to carry out “the comparing service quality between private and public hospital”. The main objective is to determine service quality factors that effecting customer preference. It consist of five factor of service quality that are tangibles, reliability, responsiveness, assurance and empathy. This research where been used the non-probability sampling techniques and simple random techniques to get the data that are require. The research population is the out patients for both hospital and the sampling frame for this research is the out patients at KPJ Ampang Puteri Specialist Hospital (Private) and Pusat Perubatan Universiti Kebangsaan Malaysia (Public). About 70 respondents (35 for private and 35 for public) were getting from the research to help for accomplish this research by answering questionnaires had been distributed to them. All the data collected through the question were analysed systematically by Statistical Package for Social Science (SPSS 16.0.1) The conclusion of this study was the outcome from the data analysis and findings. Through the research, it shows based on Frequency and Descriptive Statistic, a clear finding and results are observed. The finding showed the most factors of service quality that most patient likes at private hospital and public hospital.